TI_GERICHTE 52.2022.212 vom 5. Oktober 2022 , Commesse pubbliche. Offerta sotto costo. Valutazione dei criteri di aggiudicazione - TI Tribunale d'appello (2022)
Commesse pubbliche. Offerta sotto costo. Valutazione dei criteri di aggiudicazione